How drama activates learning : contemporary research and practice - Anderson, Michael, 1969-; Dunn, Julie, 1959- (Bloomsbury Academic, 2013)
"How Drama Activates Learning: Contemporary Research and Practice draws together leaders in drama and education from across the globe, including authors from Europe, North America and Australasia to explore the transformations that can be achieved across a diverse range of learning areas when the processes of drama education are applied, enlivening and enriching a range of learning contexts. The range of areas explored includes: History Literacy and literature Creativity and imagination Science Citizenship, democracy and social justice education language learning Human relationships Conflict management Drawing on a range of theoretical perspectives, the contributors present detailed case study material that outlines these processes in action, before the volume editors synthesize the key findings generated"--